Do Older Female Ex-Prisoners Participate in the Labour Market? - Błędowski, Piotr (Women & criminal justice, 2024)
We investigate labor force participation of female ex-offenders who served their first sentence late in life. We investigate whether ex-offenders’ labor market attachment differed before and after their imprisonment, and whether being employed helped them avoid or postpone recidivism. We contribute to the existing research on this topic by examining a very specific, yet disadvantaged group of workers in a longitudinal study using administrative data from all public employment offices in Poland for the period of 1 June 2004 to 31 December 2017. We find that while the older female ex-prisoners were indeed loosely attached to the labor market, being employed decreased their risk of a second imprisonment by 90%, and postponed recidivism. We also show that the multidimensionality of job quality matters, and that being attached to the labor force mattered most for ex-offenders with only one conviction, which should be taken into account in formulating social reintegration policies.